Synergistic Effect of Community Environment on Cognitive Function in Elderly People - Tao Shen; Ying Li; Man Zhang (Buildings)
With rapid global aging, the community environment has become a critical factor influencing cognitive health in older adults. However, most existing studies focus on single environmental attributes and rely on linear analytical methods, which fail to capture the complex and synergistic effects of community features. Guided by an integrated theoretical perspective on environmental psychology, aging, and cognitive health, this study examines how multiple community environmental factors jointly affect cognitive function in elderly people. A case study was conducted among 215 older residents in Shanghai, China. An exploratory factor analysis (EFA) identified the following five key dimensions of community environment: pedestrian friendliness, blue–green spaces, infrastructure, space attractiveness, and safety. We then applied both Partial Least Squares Structural Equation Modeling (PLS-SEM) and Fuzzy Set Qualitative Comparative Analysis (fsQCA) to reveal linear and configurational relationships. The findings showed that pedestrian friendliness, blue–green spaces, and space attractiveness significantly enhance cognitive health, while fsQCA highlighted multiple pathways that underscore the non-linear and synergistic interactions among environmental features. These results provide theoretical insights into the mechanisms linking community environments and cognitive function and offer practical guidance for designing age-friendly communities.